Faktor – Faktor yang Berhubungan dengan Kejadian Unmet Need KB pada Pasangan Usia Subur di Kelurahan Sulanjana Jambi - Indah Tyandi, Chairunnisa; Hubaybah, Hubaybah; Putri, Fitria Eka (Jurnal Kesmas Jambi, 2023)
Unmet need for family planning is a couple of childbearing age who do not want children, want children with a distance of 2 but do not use contraception. The Sulanjana Village has the highest unmet need for KB rating in East Jambi at 38.40%. The study aims to determine the relationship between age, education, employment status, income, and attitudes towards family planning, with the incidence of unmet need for family planning in couples of childbearing age in Sulanjana Village, East Jambi District, Jambi City in 2023This study used a cross-sectional design with a sample of 78 respondents taken using accidental sampling technique. The sample is married women of childbearing age aged 19-49 years. data collection was carried out February-March 2023 by interviewing using a questionnaire. Data processing was performed univariately and bivariately using the SPSS chi-square test. the results of the analysis show a relationship between income (P-value=0.024), and attitude (P-value=0.010), while the variables are age (P-value=0.820), education (P-value=1.000), occupation (P-value= 634) there is no relationship with the incidence of unmet need for family planning in couples of childbearing age in the Sulanjana Village, DistrictEast Jambi Jambi City.to increase knowledge, attitudes in socializing and educating the community regarding the importance of participating in family planning programs and using contraceptives, not only wives but husbands also participate.